Studi Pemulihan Dan Pengembangan Ekonomi Kreatif Sub-Sektor Kuliner Pasca Pandemi (Covid-19) Dalam Menunjang Pertumbuhan Ekonomi Di Provinsi Sulawesi Tenggara - Arlita Aristianingsih Jufra (Universitas Muhammadiyah Kendari, 2020)
Covid-19 has globally been declared as a pandemic, and does globally have an impact on the economy including Indonesia. It makes Indonesia’s economic growth rate become slower in all sectors including Creative Economy, in this case, for instance culinary sub-sector MSME (Micro, Small, And Medium Enterprise). This research explores the impact of Covid 19 pandemic toward culinary sub-sector of creative economy-based MSME in South East Sulawesi. It was to find out what steps that could be conducted by the government in respect of covid-19 pandemic problem. This research applied quantitative and literary methods to collect the data. The process to retrieve or collect data used the survey method and through the literary method. The presented data was collected from questionnaires, literary reviews from books, government official websites, official reports from international organizations, official news websites, and the processed data from other relevant sources. The time-span of this research was March 2020 (the beginning of this pandemic outbreak in Indonesia) until the middle of June 2020. The finished data was the graphical data with the descriptive narration. Overall, the result showed that there were two elements which became the problems regarding Covid-19 pandemic toward the people in the culinary sub-sector MSME, namely Human Resources and Goods and Services products. The government could conduct a scheme or take the steps to solve the problems, such as giving rebates on electricity bills, loan instalment suspension, supervising the groceries supplies in the markets, and keeping paying attention to MSME people who closed their business due to the pandemic so that they could transform or make a new business.